THE IMPORTANCE AND POSSIBILITIES OF DISTANCE EDUCATION IN THE EDUCATIONAL PROCESS - Rajabova, Zukhra; Abdullaeva , Gulchekhra (MMIT Proceedings, 2023)
The importance of distance learning and distance education in the education of young people in our country is increasing day by day. Distance education is a type of education in which the teacher and the student are connected by distance or time, using information technologies. Nowadays, at a time when information technology is rapidly developing in the society, the question of developing the educational system in accordance with the requirements of this development and thereby producing mature specialists is considered one of the most important tasks. In this regard, this article analyzes the problematic situations, controversial issues and views that still exist on this topic.